2020
DOI: 10.1177/0003134820951482
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on the Efficacy and Safety of Laparoscopic Surgery for Large Gastric Gastrointestinal Stromal Tumors

Abstract: Background The aim of this study was to conduct a meta-analysis comparing the safety and feasibility of laparoscopic versus open resection for gastric gastrointestinal stromal tumors (GISTs) larger than 5 cm. Method We searched the Cochrane Library, PubMed, and Embase for relevant articles. Randomized and nonrandomized clinical trials were identified and included in this study. Searching for related articles on large GIST (>5 cm) for laparoscopic resection (laparoscopic group [LAPG]) and open resection (ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The increasing incidence of GISTs, a form of soft tissue sarcoma, is becoming a signi cant concern in the medical eld, likely due to enhanced health awareness and advancements in diagnostic methods 21 . The evolution of therapeutic strategies for GISTs, transitioning from conventional surgical resection to a combination of surgery and targeted therapies such as imatinib, represents a signi cant advancement in this domain 22,23,24 . Despite these developments, the risk of recurrence or metastasis in high-risk GIST patients remains a critical issue, adversely affecting their quality of life and survival 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The increasing incidence of GISTs, a form of soft tissue sarcoma, is becoming a signi cant concern in the medical eld, likely due to enhanced health awareness and advancements in diagnostic methods 21 . The evolution of therapeutic strategies for GISTs, transitioning from conventional surgical resection to a combination of surgery and targeted therapies such as imatinib, represents a signi cant advancement in this domain 22,23,24 . Despite these developments, the risk of recurrence or metastasis in high-risk GIST patients remains a critical issue, adversely affecting their quality of life and survival 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, with the development of techniques and energy devices, laparoscopic surgery is no longer limited by the tumor size. Laparoscopic surgery provides a clear and broad field of vision that facilitates more sophisticated dissection and timely treatment of intraoperative bleeding, thereby realizing equivalent oncological safety and even better 5-year disease-free survival for large tumors (> 5 cm) compared to open surgery[ 7 - 9 ]. In our study, 26.6% of the tumors in the LR group were large tumors, and we also used this for two cases with preoperative target therapy for one year.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, open surgery was considered the main treatment for extensive tumors, and laparoscopic surgery was reserved for small tumors (< 5 cm). However, with advanced laparoscopic techniques, tumor size is no longer a restricting factor; even large tumors can be successfully removed via laparoscopic surgery[ 7 - 9 ]. For certain tumors in unfavorable locations[ 10 ], Hiki et al [ 11 ] introduced laparoscopic and endoscopic cooperative surgery (LECS), with the combined advantages of endoscopy and laparoscopy[ 12 ], which helps to achieve precise localization, minimal resection, and functional preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that endoscopy-assisted laparoscopic surgery provides effective recovery for GIST patients without serious complications [ 17 , 18 ]. It has also been reported that such surgical protocol could minimize surgical trauma to ensure higher safety [ 19 , 20 ]. Results of the present study showed superior coagulation indexes in the eligible patients given endoscopy-assisted laparoscopic gastrectomy versus laparoscopic gastrectomy alone, which indicates the benefits of the combined method in the protection and enhancement of coagulation functions.…”
Section: Discussionmentioning
confidence: 99%